The Library of Ignace Oginski (1755–1786): A Reflection of Geneological and Religious Identity - Pacevičius, Arvydas (Knygotyra, 2019)
This article examines the development and the contents of the library of Ignacy Oginski, appointed elder of the Darsūniškis and Vaiguva communities; his collection of books is discussed with an emphasis on how the sense of self as well as geneological and religious identity are expressed. The library of I.Oginski is discussed within the context of the history of his family and closest relatives as well as his connections with the Bernardines of Trakai. The bibliographical and provenance analysis is founded on I. Oginski’s books, which are stored in Vilnius University Library (10 specimens); also published at the end of this paper is a list of books bestowed by I. Oginski to the Trakai Bernardine Monastery, which itself was added into the 1787 catalogue of the monastery’s library. It was determined that I. Oginski belonged to the third order of the Franciscan tertiaries and was a financial affairs trustee (i.e., a syndic, Lat. Sindicus Apostolicus) of the Trakai Bernardine Monastery, which he, together with his mother Antonina Oginska, had amply sponsored and to which he bequeathed upon death a sum of 7 thousand Lithuanian Zloty. I. Oginski bestowed his personal library, which consisted of 201 volume, to the Bernardines on March 29, 1786 based on a testament written in Kruonis. It contained not only the more traditional printed materials but also some sheet music characteristic of courtly culture, ledgers, and silva rerum manuscripts. Noteworthy is the prayer “On the Appeal for a Fulfilling Life” (Pol. O uproszenie stanu życia przyzwoitego), handwritten by I. Oginski himself. A large part of the library consisted of ascetic lectures, spiritual exercises, and sermons typical of the Bernardine monks, but the collection was not limited in this aspect, as it also had some secular French works from the Enlightenment period and textbooks printed by the publishing house of the Vilnius Piarists. The considerable number of historical works and books containing dedications with references to the merits of the Oginskis to the state and the Church shows that I. Oginski was particularly attentive of his family history. Generally, the library demonstrates quite clearly a promotional-religious aspect of I. Oginski’s genealogical sense of self and identity. And here, too, the ascetic literature supplements the data from other sources regarding I. Oginski’s piety and his belonging to the tertiary community. The carried out study of I. Oginski’s identity and his personal library’s development and the relevant associations confirms the available possibilities of using the approaches and methodologies of cultural anthropology and social communication in book science studies.